Development Paradox: The Effect of Economic Growth, Unemployment, and Human Development on Inequality - Faisal, Muhammad Faisal; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2026)
Income inequality remains a critical challenge in economic development that can hinder inclusive growth, making this issue urgent to address. This study analyzes the effect of economic growth, open unemployment rate, and the Human Development Index (HDI) on income inequality. The method used is panel data regression with a Fixed Effect model across five districts/cities for the 2015–2024 period. The results show that economic growth does not have a significant effect on inequality, indicating the phenomenon of jobless growth in the tourism and service sectors. Conversely, the open unemployment rate has a positive and significant effect on income inequality. A unique finding shows that HDI also has a positive and significant effect, confirming the phenomenon of elite capture, where the benefits of human development tend to be concentrated in certain groups and regions. As an implication, regional governments need to transform the service sector to be more inclusive, empower MSMEs in areas with high unemployment, and decentralize public facilities to southern regions to encourage a more equitable distribution of income.